SURVEY OPINI MASYARAKAT TENTANG ANAK BERKEBUTUHAN KHUSUS DI KELURAHAN MEDOKAN SEMAMPIR KECAMATAN SUKOLILO KOTA SURABAYA - IKRAR PRADANA ADIKUSUMA PUTRA, RAHMAD (Jurnal Pendidikan Khusus, 2016)
ABSTRACT The characteristics differences to society group happened because there was different background from each member individual in the group of society such as education, profession, and so on. This also happened to society group in Medokan Semampir where the region had diversity citizens consisted of variety of the background such as education, profession, and many others. Based on the explanation above, the researcher took the research focus about what the society’s opinion was toward special need children in Medokan Semampir village Sukolilo district Surabaya city. This research had purpose to obtain the data and information from the society of Medokan Semampir village Sukolilo district Surabaya city regarding with the opinion about the special need children generally or specifically. The data source in this research was the society of Medokan Semampin village Sukolilo district Surabaya city either male or female with the age range 20 – 50 years. The research method used was descriptive qualitative and the technique of data analysis was qualitative in according to Miles dan Huberman. The research result found that: (1) the society in Medokan Semampir village Sukolilo district Surabaya city stated that special need children were blind, deaf, mute, and hyperactive who needed affection more than the normal; (2) the citizen’s knowledge in the region about special need children was still limited in blind, hearing impairment, and autism; (3) the citizen’s response was limited to giving treatment normally when they met special need children; (4) the citizen in Medokan Semampir village Sukolilo district Surabaya city did not really view the government’s role yet to the special need children; (5) the citizen in that village still felt strange and did not recognize the existence of inclusion education service in the region yet; (6) the citizen could not give the idea and response yet about the special need children because of the lack of socialization; (7) the citizen was still confused about the prospect of special need children in the future; (8) the citizen gave suggestion and critic to education service to be better; (9) the citizen hoped there was socialization about special need children and the form of inclusion education service.   Keywords:  society’s opinion, Special need children